2009
DOI: 10.1103/physrevd.79.104005
|View full text |Cite
|
Sign up to set email alerts
|

Massive fermion emission from higher dimensional black holes

Abstract: We study the effect of extra dimensions on the process of massive Dirac fermion emission in the spacetime of (4 + n)-dimensional black hole, by examining the Dirac operator in arbitrary spacetime dimension. We comment on both bulk and brane emission and find absorption cross section and luminosity of Hawking radiation in the low-energy approximation.PACS numbers: 04.50.+h, 04.70.Dy I. INTRODUCTIONScientists have devoted many years to the ongoing quest to unify the forces in Nature. Higher-dimensional theories … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…For this spacetime it was also revealed that the absorption probability depended on mass of the emitted field, that is, the absorption probability decreases or increases depending on the range of energy when the mass of the field increases. Also, was observed that the absorption probability increases for higher radius of the event horizon [29].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…For this spacetime it was also revealed that the absorption probability depended on mass of the emitted field, that is, the absorption probability decreases or increases depending on the range of energy when the mass of the field increases. Also, was observed that the absorption probability increases for higher radius of the event horizon [29].…”
Section: Discussionmentioning
confidence: 90%
“…As we mentioned, the reflection and transmission coefficients depend on the behaviour of the radial function both, at the horizon and at the asymptotic infinity and they are defined by (28) where F is the flux, and is given by (29), and yields…”
Section: Reflection Coefficient Transmission Coefficient and Absorptmentioning
confidence: 99%
See 1 more Smart Citation
“…For this spacetime, it was also revealed that the absorption probability depended on the mass of the emitted field, that is, the absorption probability decreases or increases depending on the range of energy when the mass of the field increases. Also, it has been observed that the absorption probability increases for higher radii of the event horizon [29]; see for instance [30,31] for the decay of Dirac fields in higher-dimensional black holes. For further reference, massive charged scalar field perturbations of the Kerr-Newman black hole background were studied in [32,33], the absorption of photons and fermions by black holes in four-dimensions in [34], the fermion absorption cross section of a Schwarzschild black hole in [35], and charged fermionic perturbations in the Reissner-Nordstrom anti-de Sitter black hole background in [36].…”
Section: Introductionmentioning
confidence: 99%
“…[28,29,30] by solving the massive Dirac equation in the background of a Schwarzschild (4 + n) higher-dimensional black hole, using a different gauge technique than the ones used there. We chose to work in the so called Cartesian gauge proposed some time ago in Ref.…”
Section: Introductionmentioning
confidence: 99%